Karawitan Artwork “Semenanjung Senja” | Karya Karawitan “Semenanjung Senja” - I Putu Prabawa Laksana Putra (GHURNITA: Jurnal Seni Karawitan, 2023)
The moment when the sun sets and rises is a precious moment of God's beautiful grace. At this point, the composer put into a work entitled "Semenanjung Senja", which means the beauty of peninsula dusk. The beauty of the ever-changing twilight at sunset, sometimes orange, sometimes rosy red, occasionally pink, combined with a genuinely charming blue sky. The beauty of this twilight finally led the composer to work on an innovative karawitan work of art. This work uses several stages from Alma M. Hawkins: exploration, improvisation and formation. This creative karawitan work uses a concept consisting of three parts: the first part describes the beauty and how the composer is amazed by the dusk, the second part describes how the composer walks along and enjoys the beauty of the sunset, and the third part is how the composer interprets the twilight atmosphere into this karawitan artwork through gamelan Semar Pegulingan and Gender Wayang. The combination of both gamelan creates a unique tone called Patet Sunaren. This innovative artwork was supported by 16 (sixteen) musicians from Mekar Seruni Studio in Banjar Sayan Delodan, Wherdi Bhuana Village, Mengwi District, Badung Regency.